Resistance to local anaesthetics administered via epidural, intrathecal and pudendal injections. Issue 2 (18th December 2022) - Jacobs, E.; Baban, N.; Emmett, L.
Summary: A primigravida presented to our institution in established labour. Her past medical history included joint hypermobility, postural orthostatic tachycardia syndrome, Raynaud's syndrome, fibromyalgia and gastroparesis. Two technically uneventful lumbar epidurals with bupivacaine and fentanyl provided no analgesia. The spinal element of a planned combined spinal and epidural was also ineffective, so alternative analgesia was offered. While this was being prepared, the obstetric team recommended an instrumental delivery. An attempted pudendal nerve block with lidocaine had no effect, and general anaesthesia was therefore provided for a lower segment caesarean delivery. We believe this is the first report of local anaesthetic resistance via three distinct routes of administration in a single patient. Resistance to local anaesthetics is unusual and is more common in patients with hypermobility spectrum disorders. This case demonstrates the unique experience of a patient with a hypermobility condition who had failed epidural, spinal and pudendal local anaesthetic. We suggest that patients with a hypermobility condition should be specifically assessed for local anaesthetic resistance as part of anaesthetic pre‐assessment, to enable early planning.